Low-cost smart antennas - Luo, Qi, 1982-; Gao, Steven; Liu, Wei, 1974-; Gu, Chao, 1986 September 24- (Microwave and wireless technologies series, 2019)
An authoritative guide to the latest developments for the design of low-cost smart antennas Traditional smart antenna systems are costly, consume great amounts of power and are bulky size. Low-cost Smart Antennas offers a guide to designing smart antenna systems that are low cost, low power, and compact in size and can be applied to satellite communications, radar and mobile communications. The authors - noted experts on the topic - provide introductions to the fundamental concepts of antennas, array antennas and smart antennas. The book fills a gap in the literature by presenting the design techniques of low-cost radio frequency (RF) smart antennas as well as approaches for implementing the hardware of the antenna and the beamforming network (BFN). A comprehensive and accessible book, Low-cost Smart Antennas not only presents an up-to-date review of the topic but includes illustrative case studies that contain in-depth explorations of the theory and technology of smart antennas. While other resources highlight the software (signal processing algorithms), this book is unique by focusing on the antenna hardware. This important book: -Offers an introduction to the most recent developments of the design of low-cost smart antennas and their applications -Presents a unique book that puts the focus on antenna hardware -Includes a variety of case studies that clearly demonstrate the implementation of current design techniques -Introduces both fundamental theories as well as more advanced topics Written for students and researchers and antenna engineers, Low-cost Smart Antennas explores the most recent advances in the field with an emphasis on antenna hardware.